The Importance of a Child's Brain Development in Mental Arithmetics and its Role in Life (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses mental arithmetic in preschool education and provides a promising platform for further education, allowing to achieve excellent intellectual and creative development results in the learning process.